Conclusions of Hungarian elite athletes' doping controls in the year of the Olympic Games in Beijing - Trombitasne Ranky, M.; Noe, J.; Frenkl, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The sportsmen have been used different medicines and dietary supplements during the trainings and competitions. Theirs quantity and quality are disputable by point of view of health protection many times. According to our opinion it is necessary systematic health education and scientific nutrition advices to fend off pressure of consuming supplements induced by the commercial advertisements and by psychological reasons. Sport background of these acting we should like help on with special data bases. In former researches we fixed information during long time (7 years) one kind of sport (athletic). In the present case, our aim gain data about medicine and supplement consumption habit and specification of Hungarian elite athletes of different discipline of sport during one Olympic year. Methods: The analyzed information based on the admissions of Doping Control Collection Form of different Hungarian elite athletes in Hungary in time from January 01 2008 to December 31 2008. The Forms are recording the names of medicines and nutrition supplements consumed by the competitors ten days prior the control. We have created a database out of these data. Results: The members of examination were representatives of 32 Olympic-, 12 Paralympics- and 5 non Olympic -disciplines. The total sum of Doping controls was 1518 (n= 851m, n=667w) out during in the given period of time. The competitors of Olympic disciplines have been participated 1396 in case n=766m (503 urine samples, 263 blood samples), n=630w (422 urine s, 208 blood s). Non Olympic sportsmen were checking 61 in case, n=43m (41 urine s, 2 blood s), n=18w (17 urine s, 1 blood s). Paralympics had controls 61 in case, n=42m, n=19w all in urine. In the period of survey only in case 70 (4.6%) hasn`t use any medicines and dietary supplements. Use of the prohibited medications with license were detected 97 (6.38%) in case. (n=50m, n=47w) Numbers of articles named by Hungarian elite athletes were investigated grouped to medicines and nutrition supplements by the athlete gender and disciplines of sports. Conclusions: It has been discovered from Doping Collecting Forms too many sports men use different non steroid medicines and pain relieves with together. After detailed analyzing of consumption of vitamins, the results showed too many competitors used by more types of vitamin complex. In our opinion there is a high rate of consumption if somebody used five or more dietary supplements in the checking period. We was detected 66 in case (n=49m and n=17w) when the number of taken supplements are over then 10. Conclusions of our examination that significant numbers of sportsmen do not used the supplements according to needs. For optimization of nutrition advices should be a theoretically accept for sports, like the standards RDA, ODI, PDI. References: D H Catlin, K D Fitch, A Ljungqvist. (2008) Journal of Internal Medicine, 264; 99-114. Ránky M. (2007) Annual Congress of the ECSS abstracts book, 502.